2014
DOI: 10.1253/circj.cj-13-0704
|View full text |Cite
|
Sign up to set email alerts
|

J Waves in Accidental Hypothermia

Abstract: 128HIGUCHI S et al. Circulation JournalOfficial Journal of the Japanese Circulation Society http://www. j-circ.or.jp he J wave, also known as the Osborn wave, 1 is a positive deflection at the terminal part of the QRS complex. Although J waves are often observed in hypothermic patients, 2 few reports have revealed the relationship between the presence of J waves and body temperature (BT). The exact BT at which J waves develop in clinical settings has not yet been determined.The J wave is noted not only in hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
2
26
0
1
Order By: Relevance
“…Higuchi et al 12 reported the prevalence of J waves and the relationship between the body temperature and J-wave amplitude in 61 patients with accidental hypothermia. They also examined the augmentation of J waves following variable RR intervals in such patients with atrial fibrillation, and found that J waves are augmented after a relatively short RR interval.…”
Section: Discussionmentioning
confidence: 99%
“…Higuchi et al 12 reported the prevalence of J waves and the relationship between the body temperature and J-wave amplitude in 61 patients with accidental hypothermia. They also examined the augmentation of J waves following variable RR intervals in such patients with atrial fibrillation, and found that J waves are augmented after a relatively short RR interval.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, J waves appeared at mild hypothermia (34°C), which was reported to be a marginal temperature for their development in the clinical setting 24 . Even at mild hypothermia, the amplitude of J waves in the inferolateral leads became augmented, leading to the development of VPCs.…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, in our case, the magnitude of J waves decreased after a long R-R interval in the same manner as that observed in a previous study of patients with hypothermia. 9 Previous studies have demonstrated that ISP, a betaadrenergic stimulant, is very effective at suppressing electrical storms related to BrS and ERS. ISP increases the I Ca current and restores the dome of the epicardial AP.…”
Section: Discussionmentioning
confidence: 99%